1996
DOI: 10.1111/j.1476-5381.1996.tb15503.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of metabotropic glutamate receptors coupled to phospholipase D in the rat hippocampus

Abstract: 1 Phospholipase D (PLD) is the key enzyme in a signal transduction pathway leading to the formation of the second messengers phosphatidic acid and diacylglycerol. In order to define the pharmacological profile of PLD-coupled metabotropic glutamate receptors (mGluRs), PLD activity was measured in slices of adult rat brain in the presence of mGluR agonists or antagonists. Activation of the phospholipase C (PLC) pathway by the same agents was also examined. 2 The mGluR-selective agonist (1S,3R)-l-aminocyclopentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 46 publications
4
71
2
Order By: Relevance
“…While both 1S,3R-ACPD and DHPG stimulate synaptosomal PLD activity, the magnitude of stimulation was lower than that described in other reports (PellegriniGiampietro et al, 1996). Also, DHPG antagonizes 1S,3R-ACPD stimulated PLD (Pellegrini-Giampietro et al, 1996), an e ect not observed in this study. The discrepancies between the agonist e ects may be accounted for by the di erent systems employed.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…While both 1S,3R-ACPD and DHPG stimulate synaptosomal PLD activity, the magnitude of stimulation was lower than that described in other reports (PellegriniGiampietro et al, 1996). Also, DHPG antagonizes 1S,3R-ACPD stimulated PLD (Pellegrini-Giampietro et al, 1996), an e ect not observed in this study. The discrepancies between the agonist e ects may be accounted for by the di erent systems employed.…”
Section: Discussioncontrasting
confidence: 52%
“…These include muscarinic stimulation of synaptosomes (Hattori & Kanfer, 1985;Qian & Drewes, 1989) and the activation of mGluRs in hippocampal and cortical slices (Boss & Conn, 1992;Holler et al, 1993;Klein et al, 1998;Pellegrini-Giampietro et al, 1996). It has also been shown recently that elevated calcium levels and GTPgS application to permeabilized synaptosomes increased PLD activity (Sarri et al, 1998) which suggests that calcium in¯ux may be required for G-protein coupled receptors activation of PLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mGluRs from groups II (mGluR2 and mGluR3) and III (mGluR4, mGluR6, mGluR7, and mGluR8) are negatively coupled to adenylate cyclase activity. In addition, an mGluR receptor coupled to phospholipase D has been identified in the hippocampus (Pellegrini-Giampetro et al, 1996). This coupling to disparate transduction pathways may underlie the different actions of mGluRs on neurodegenerative processes.…”
mentioning
confidence: 99%
“…A potential novel metabotropic glutamate receptor coupled to phosphoinositide turnover has been observed in rat brain; it is activated by 4-methylhomoibotenic acid (ineffective as an agonist at recombinant Group I metabotropic glutamate receptors), but resistant to LY341495 (Chung et al, 1997). There are also reports of a distinct metabotropic glutamate receptor coupled to phospholipase D in rat brain, which does not readily fit into the current classification Pellegrini-Giampietro et al, 1996). 3-cyano-N-(1,3-diphenyl-1H-[pyrazol-5-yl)benzamide; CHPG, 2-chloro-5-hydroxyphenylglycine; CPCCOEt, cyclopropan[b]chromen-1a-carboxylate; 4CPG, CPPHA,methyl]phenyl}-2-hydroxybenzamide; DCG-IV, (2S,1′R,2′R,3′R)-2-(2,3-dicarboxycyclopropyl)glycine; (S)-3,4-DCPG, (S)-3,4-dicarboxylphenylglycine; DFB, 3,3′-difluorobenzaldazine; DHPG, S-3,5-dihydroxyphenylglycine; DMPPP, 3,5-dimethyl pyrrole-2,4-dicarboxylic acid 2-propyl ester 4-(1,2,2-tri-methyl-propyl) ester; EGLU, (s)-a-ethylglutamate; EM-TBPC, (1-ethyl-2-methyl-6-oxo-4-(1,2,4,5-tetrahydrobenzo[d]azepin-3-yl)-1,6-dihydropyrimidine-5-carbonitrile; fenobam, N- (3-chlorophenyl)-N′-(4,5-dihydrol-1-methyl-4-oxo-1-H-imidazole-2-yl)-urea; 3HPG, 3-hydroxyphenylglycine; [ 11 C]-JNJ-16567083, (3-ethyl-2-[ 11 C]methyl-6-quinolinyl)(cis-4-methoxycyclohexyl) methanone; JNJ16259685, (3,4-dihydro-2H-pyrano[2,3]…”
Section: Glutamate Metabotropicmentioning
confidence: 99%